Gerd Walter - SPD - RSCG, Butter, Rang; Sozialdemokratische Partei Deutschlands (SPD), Vorstand, Referat Öffentlichkeitsarbeit, Bonn; Wullenwever-Druck, Lübeck
Bemerkungen: Eindruckplakat ohne Eindruck